Functional health literacy in Spanish-speaking Latinas seeking breast cancer screening through the National Breast and Cervical Cancer Screening Program - Samantha Garbers; Karen Schmitt; Anne Marie Rappa; Mary Ann Chiasson (Dove Medical Press, 2009)
Samantha Garbers1, Karen Schmitt2, Anne Marie Rappa2, Mary Ann Chiasson11Public Health Solutions, New York, NY, USA; 2Columbia University Breast Cancer Screening Program, New York, NY, USABackground: This analysis examines the association between functional health literacy and follow-up after mammography among women receiving breast cancer screening at a National Breast and Cervical Cancer Early Detection Program site in New York City that provides universal bilingual case management.Methods: A total of 707 Latinas who spoke Spanish as their primary language completed a survey of health and demographic characteristics and the Test of Functional Health Literacy in Spanish (TOFHLA-S). Survey results were matched with clinical outcome data.Results: Among the survey participants, 98% were foreign-born and 99% had no health insurance. While the study found significant differences in access to health information and past screening behavior, women without adequate health literacy in Spanish were no less likely to receive clinical resolution of abnormal mammograms within 60 days (81.8% overall; n = 110) or to return for a repeat mammogram within 18 months (57.2% overall; n = 697). In fact, among those referred for a Pap test (n = 310), women without adequate health literacy were more likely to receive a Pap test within 60 days of their mammogram than those with adequate health literacy (82% compared to 71%, OR: 1.83, 95% CI: 1.04–3.22).Discussion: The lack of significantly lower follow-up outcomes among women with inadequate and marginal functional health literacy in this population of primary Spanish-speaking Latinas suggests that, once women have accessed screening services, programmatic approaches may exist to mitigate barriers to follow-up and to ensure optimal cancer screening outcomes for women of all literacy levels.Keywords: health literacy, mammography, Latinas, case management, cancer screening